În cazul general:
[tex]ax^2+bx+c = 0\\~
\Delta = b^2-ac\\~
x_1 = \frac{-b+\sqrt{\Delta}}{2a}\\~
x_2 = \frac{-b-\sqrt{\Delta}}{2a}[/tex]
Ecuația admite soluții reale dacă delta e mai mare sau egală cu 0.
În cazul nostru:
[tex]ax^2+(3a+1)x+a+3=0 \\~
\Delta = (3a+1)^2-4(a+3)a\\~
\Delta = 9a^2+6a+1-4a^2-12a\\~
\Delta = 5a^2-6a+1\\~
5a^2-6a+1 \geq 0\\~
5a^2-6a+1=0\\~
\Delta_a = 36-20 = 16 = 4*4\\~
a_1 = \frac{6+\sqrt{16}}{10} = 1\\~
a_2 = \frac{2}{10} = \frac{1}{5}\\~
a \in (-\infty,\frac{1}{5}] \cup [1,\infty)[/tex]